Incidence and Risk Factors of Postcontrast Acute Kidney Injury in Patients with Acute Ischemic Stroke. (1st April 2020) - Chusiri, Sirichai; Chutinet, Aurauma; Suwanwela, Nijasri Charnnarong; Puttilerpong, Chankit
Abstract : Background . Multimodal computed tomography (CT) guides decision-making regarding use of thrombolytic agents in acute ischemic stroke patients. However, postcontrast acute kidney injury (PC-AKI) is a potential adverse effect of the contrast media used, which may require hemodialysis and cause a longer hospital stay. The incidence and risk factors of PC-AKI in acute ischemic stroke patients, particularly in Thailand, remain unclear. Goal . We aimed at determining the incidence and risk factors of PC-AKI in patients with acute ischemic stroke undergoing multimodal CT. Methods . We conducted a retrospective review of Thai acute ischemic stroke patients admitted to the King Chulalongkorn Memorial Hospital between January 2014 and December 2017 who received multimodal CT and thrombolytic treatment with alteplase. Result . Overall, 109 patients were included for analysis; eight patients (7.3%) developed PC-AKI. Estimated glomerular filtration rate eGFR ≤ 30   mL / min and mechanical thrombectomy were risk factors significantly associated with PC-AKI. Conclusion . The incidence of PC-AKI in a real practice setting did not differ from previous reports. Two factors were associated with PC-AKI, eGFR ≤ 30   mL / min and mechanical thrombectomy. Patients without these risk factors may not need to wait for the results of renal function testing prior to multimodal CT.